TRACING ENTITIES OF ARABIC IN THE QUR’AN - Wahida, Besse; Nuur, Khaerun Nisa; Ansori, Ibnu Hajar (Jurnal Adabiyah, 2021)
This article examined how the Qur’an talks about the Arabic used in it, its essence, existence, and urgency, departing from the dialectic of the foreign languages existence in the Qur’an. This study was literature research using an interpretive approach with the method maud}u>'i which research objects were verses about the Arabic Quran, and were analyzed descriptively. The results showed that the essence of the Arabic language used in the Quran is Arabic which was fluent and clear, which was understood and popular among Arabs when the Qur'an was revealed. The diction used is the word 'arabiy, which is an adjective (s{ifat)  connected to words qur'a>n, lisa>n, and hukman repeated eleven times. The existences of Arabic in the Qur’an are Arabic fus}h}ah, Arabic al-Qur'an as Miracle, and Arabic as the language of sharia/law. While the urgencies of Arabic use in the Qur’an is seen from the word 'arabiy followed by the word la'alla (لعل) and li (ل) repeated seven times and its means are the key to understand the Qur’an, encouraging thinking, encouraging spirituality. The results of this study were expected to be a common thread for the two groups arguing about the existence of foreign languages in the Qur’an.Keywords: Arabic, the Qur’an, Entity.